2008
DOI: 10.1002/mds.21826
|View full text |Cite
|
Sign up to set email alerts
|

Action‐induced clonus mimicking tremor

Abstract: Action tremor has been described in cerebellar, task-specific, dystonic, or Holmes tremor. We report 2 patients who developed unilateral kinetic or isometric action tremor of the upper extremity, following cervical spondylotic myelopathy and capsular ischemic stroke. Slight motor weakness and spasticity with exaggerated tendon jerks and passive stretch-induced clonus were present on the same limb. The central motor pathways lesions might have been responsible for a hyperexcitability of the stretch-reflex arc a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 10 publications
2
3
0
Order By: Relevance
“…This finding is clearly supported by the literature, which reports a close relationship between stroke and spasticity and the incidence of clonus or tremor (Fraix, Delalande, Parrache, Derambure, & Cassim, 2008;Wu, et al, 2006).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This finding is clearly supported by the literature, which reports a close relationship between stroke and spasticity and the incidence of clonus or tremor (Fraix, Delalande, Parrache, Derambure, & Cassim, 2008;Wu, et al, 2006).…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, 93.8% of the participants agreed that b765, Involuntary movement functions, is a problem treated by occupational therapists that is not included in the ICF Core Set for stroke. This finding is clearly supported by the literature, which reports a close relationship between stroke and spasticity and the incidence of clonus or tremor (Fraix, Delalande, Parrache, Derambure, & Cassim, 2008;Wu, et al, 2006).…”
Section: E1451supporting
confidence: 89%
“…This finding is clearly supported by literature, which reports a close relationship between stroke and spasticity (hypertonicity) and the incidence of clonus or tremor. 42,43 In addition, validation studies have identified this ICF category as being relevant for occupational therapists 44 and physicians. 45 Regarding the ICF category "b780 Sensations related to muscles and movement functions," which is not represented in the ICF Core Set for stroke, again a high consensus among the participants was found.…”
Section: Extended Icf Core Set For Stroke From Physical Therapists' Pmentioning
confidence: 98%
“…Clonus is a 5–7 Hz rhythmic involuntary movement that typically occurs in response to a suddenly applied passive stretch on the limb. It might mimic action tremor, but clonus only presents during a passive movement or forceful contraction and is associated with hyperreflexia and spasticity [ 20 , 21 ]. Indeed, the spectrum of hyperkinetic movements are clinically overlapping, starting from the most regular and rhythmic movements in tremor to irregular tremor, high-frequency myoclonus, and irregular jerky movements in typical myoclonus.…”
Section: Step 1: Identify the Real Tremulous Movements And Differenti...mentioning
confidence: 99%